Структурные механизмы замещения хряща в развивающемся скелете - Мажуга, П.М. (Вестник зоологии, 1977)
Development of the humerus and femur as well as mechanisms of the enchondral process were studied in albino rats and calves. Invasion of blood vessels into cartilage occurs by means of the capillary terminals break into swollen eiondrocytes, which is favoured by hydrostatic pressure inside the swollen chondrocytes and resorption of the cartilage matrix by perivascular cells. In the vacant cavity of chondrocytes the cells of the invading vascular terminal arrange in a strict order; osteoblasts differentiate from perivascular cells adjoining the walls of the cartilagionous lacuna. A sinulacunar system of the bone marrow vessels is formed in the enchondrial process by means of the subsequent invasion of capillary terminals into the swollen chordrceytes.